2016
DOI: 10.1007/s11094-016-1431-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Antimicrobial Activities of Sanguisorba officinalis L. Extracts

Abstract: Sanquisorba officinalis has been used internally for the treatment of intestinal infections and duodenal ulcers, as well as hemorrhoids, phlebitis and varicose veins and female disorders, and topically to heal wounds, burns, and ulcers. In our study, the antioxidant and antimicrobial activities, as well as quantitative analysis of polyphenols (phenolic acids, flavonoids and total polyphenols) in methanol and aqueous extracts from S. officinalis herbs are presented. A correlation between the antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
(12 reference statements)
1
20
0
Order By: Relevance
“…Regarding the effect of the tested substrates, root extracts from plants grown on the peat : perlite (2 : 1 v/v) substrate had lower MIC values than the other substrates, except for the cases of S. aureus where streptomycin had the lowest values (0.04 μg mL −1 ), whereas the lowest MBC values were observed for the peat and peat : perlite (2 : 1 v/v) substrates. Gawron-Gzella et al 40 reported that extracts from S. officinalis exhibited antimicrobial activity against the strains of various bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Micrococcus luteus, Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa) with MIC values ranging between 0.07 and 2.50 mg mL −1 . In another recent study, Ginovyan et al 41 also reported that the extracts from S. officinalis revealed antibacterial activity against Pseudomonas aeruginosa at the concentration of 64 μg mL −1 .…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Regarding the effect of the tested substrates, root extracts from plants grown on the peat : perlite (2 : 1 v/v) substrate had lower MIC values than the other substrates, except for the cases of S. aureus where streptomycin had the lowest values (0.04 μg mL −1 ), whereas the lowest MBC values were observed for the peat and peat : perlite (2 : 1 v/v) substrates. Gawron-Gzella et al 40 reported that extracts from S. officinalis exhibited antimicrobial activity against the strains of various bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Micrococcus luteus, Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa) with MIC values ranging between 0.07 and 2.50 mg mL −1 . In another recent study, Ginovyan et al 41 also reported that the extracts from S. officinalis revealed antibacterial activity against Pseudomonas aeruginosa at the concentration of 64 μg mL −1 .…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The most representative and commonly used species of this genus are Sanguisorba minor Scop. (small burnet) and Sanguisorba officinalis L. (great burnet) which are native in the Mediterranean basin and other areas of the world (Gawron-Gzella et al, 2016;Karkanis et al, 2019). The leaves and roots of these species contain a wide variety of bioactive compounds such as gallic acid, ellagic acid, (+)-catechin, lambertianin C, sanguiin H-10, and ziyuglycoside II (Karkanis et al, 2019;Lkhagvasuren & Kim, 2019;Tan et al, 2019;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SOR is known to be effective against skin diseases, including urticaria, eczema, and allergic dermatitis [ 30 ], and against numerous bacteria [ 31 , 32 , 33 ]. However, antibacterial activity against P .…”
Section: Introductionmentioning
confidence: 99%